Determinants of sustainable software practices in the Malaysian electronic industries - Abdul Aziz, Nor Azah; Giweze Chukwuyem (Human Resource Management Academic Research Society, 2022)
The issues of software sustainability are considered a crucial factor and require adequate resolutions to effectively promote the lifecycle of software development. Unfortunately, there has been a slow progression of sustainability software system implementation regarding the modern system. Hence, this study focuses on investigating the determinant of sustainable software practices in the electronic industry of Malaysia. Based on the study’s objective, a conceptual model helped to develop following GREENSOFT Reference Model framework. Furthermore, a quantitative approach utilises data gathering and survey data collected through questionnaire distribution among software practitioners and users in the electronic industry. The study used a total of 250 samples with the aid of the SmartPLS approach using version 3.0. The outcome of this study shows that all investigative factors that include; software governance, strategy, practitioners and knowledge accessibility predicted significantly towards sustainable software practices. In addition, the path coefficient result shows that software practitioners were the most influencing factor, followed by software strategy. Hence, the study’s outcome would help offer some contributions and enhance awareness for policymakers in the respective research area and assist in the electronic industry’s application and practices of sustainable software implementation effectively.